PENGARUH PEMBERIAN INFUSED WATER KURMA TERHADAP PERUBAHAN KADAR KALIUM PADA MAHASISWA POLTEKKES KEMENKES YOGYAKARTA DENGAN PREHIPERTENSI - Safia Wahyu Pratiwi; Weni Kurdanti; Idi Setyobroto (Medika Respati : Jurnal Ilmiah Kesehatan, 2021)
Effect of Infused Water Dates to Change Potassium Levels in The Students of Yogyakarta Ministry of Health with Prehypertension Background. Hypertension not only occurs in the age of adulthood or elderly but can occur from adolescent age. Riskesdas results in 2018, the prevalence of hypertension at age ≥ 18 years in Indonesia showed an increase from the year 2013 which is from 25.8% to 34.1%. According to research, serum potassium levels in patients with hypertension are lower than those with normal blood pressure. Dates can be used as alternative hypertension treatment, one example is made infused water. The introduction of infused water dates is one way to increase the intake of potassium as well as potassium levels in the blood so it is hoped that the increased intake can lower blood pressure. Objectives. To determine the influence of infused water dates on the change of potassium levels in the students of Yogyakarta Kemenkes Poltekkes. Method. This research is quasi experiment by using one group before and after. The research took place in February 2020. The research population is the level student of the Poltekkes Kemenkes Yogyakarta, with a sample of 21 people. Data analysis using Wilcoxon test. Results. Average levels of potassium before intervention is 4,024 ± 0,4847 and average levels of potassium after intervention is 4,276 ± 0,2322. The results showed the influence of infused water dates on potassium levels (P = 0,002).  Conclusion: There is the influence of infused water dates on the change of potassium levels in students.